Comparative Study on Selenium and Volatile Compounds in Selenium-Enriched Cardamine violifolia Pickles Fermented by Three Distinct Methods - Jue Gong; Shen Rao; Xiaomeng Liu; Shuiyuan Cheng; Xin Cong; Dingxiang Zhu (Fermentation)
Cardamine violifolia is a selenium (Se)-rich vegetable crop belonging to the Brassicaceae family. This study investigated the Se concentration and volatiles in the fresh (CK) C. violifolia, natural fermented (NF), Lactiplantibacillus plantarum (LP), and Leuconostoc mesenteroides (LM) fermented C. violifolia pickles. Results showed that fermentation promoted the levels of selenocysteine, methyl selenocysteine, and selenate. A total of 648 volatile compounds were found, including 119 terpenoids, 105 heterocyclic compounds, 103 esters, and 65 hydrocarbons. Differential analysis of volatiles indicated that fermentation induced the release of volatiles when compared to CK, whereas volatile profiles in LM and NF pickles showed notable differences from LP pickles. SeCys2, MeSeCys, and selenate significantly correlated to several volatile compounds, implying that Se metabolism may affect the formation of volatiles. Conclusively, fermentation promoted the release of aroma and bioactive volatiles and the degradation of unpleasant and harmful substances in C. violifolia pickles.